(untitled) - Curzon, Susan Carol (New York, 1989)
Contain includes: conceptualizing; preparing the organization; organizing the planning group; planning; deciding; managing the individual; controlling resistance; implementing; evaluating.
Keywords: Library planning,Library administration,Library personnel management,Organizational change,Library science; Management,Technological innovations,Management